THE USE OF JOURNAL WRITING IN TEACHING RECOUNT TEXT - Resy Sinthianuary; Regina Regina; Eusabinus Bunau (Universitas Tanjungpura, 2020)
Abstract The aim of this research is to find out whether or not Journal Writing is effective in teaching writing recount text. This research applies a pre-experimental study with pre-test, post test and three meeting of treatments. The sample of this research is 24 students of class VIIID at SMP Negeri 24 Pontianak who was chosen by the suggestion of English teacher there. The data were collected using the measurement technique and the tool of data collection was a written test. The research findings showed that the mean score of the students’ pre-test was 49.79while the post-test was 63.04. The difference of the students’ mean score of pre-test and post-test was 13.25. It indicated that the ability of the students increased after the treatment was conducted. The result of the effect size (ES) was 0.3, which was categorized as a modest effect (ES>0.3). It proved that the alternative hypothesis was accepted. It can be concluded that the Journal Writing is modestly effective toteach students’ writing recount text.Keywords: Journal Writing, Recount Text, Teaching Writing